The effect of electric field on important food-processing enzymes : comparison of inactivation kinetics under conventional and ohmic heating - Castro, Inês (2004)
This work deals with the determination of the inactivation kinetics of several enzymes, most of them used as time-temperature integrators in the food industry. The tested enzymes were polyphenoloxidase, lipoxygenase, pectinase, alkaline phosphatase, and β-galactosidase, and the inactivation assays were performed under conventional and ohmic heating conditions. The thermal history of the samples (conventional and ohmically processed) was made equal to determine if there was an additional inactivation caused by the presence of an electric field, thus eliminating temperature as a variable. All the enzymes followed 1st-order inactivation kinetics for both conventional and ohmic heating treatments. The presence of an electric field does not cause an enhanced inactivation to alkaline phosphatase, pectinase, and β-galactosidase. However, lipoxygenase and polyphenoloxidase kinetics were significantly affected by the electric field, reducing the time needed for inactivation. The results of the present work can be used industrially to determine processing effectiveness when ohmic heating technology is applied.